Social deprivation as a risk factor for manipulation under anesthesia following total knee arthroplasty - Balachandran, Uma; Stern, Brocha Z; Dhanjani, Suraj; Poeran, Jashvant; Hayden, Brett; Moucha, Calin S (The Journal of Knee Surgery)
Background: Manipulation under anesthesia (MUA) is an undesirable outcome after total knee arthroplasty (TKA). Black patients have higher odds of MUA than White patients. Social deprivation is also linked to worse TKA outcomes. We examined the associations between an area-level and person-level indicator of social deprivation and odds of MUA within one year after TKA. Methods: This retrospective cohort study included fee-for-service Medicare beneficiaries 65+ (Medicare Limited Data Set, 5% claims) undergoing unilateral inpatient or outpatient primary elective TKA in 2016-2020 with an accompanying diagnosis of knee osteoarthritis. Area-level social deprivation was assessed using county-level Social Deprivation Index (SDI). Person-level social deprivation was operationalized as dual Medicare/Medicaid eligibility. We assessed the relationship between social deprivation and 1-year MUA in two mixed effects generalized linear models with a binary distribution and logit link. We report adjusted odds ratios (OR) and 95% confidence intervals (CI). Results: Our cohort included 34,948 TKA patients (median age 73 [IQR 69-77]; 63.4% women). Median SDI was 42 (IQR 20-66); 4.7% were dual-eligible. There were 758 cases of MUA (2.2%). Median time to MUA was 63.5 days (IQR 49-91). Odds of MUA receipt were significantly lower for the most deprived quintile compared with the second most deprived quintile (OR 0.75; 95% CI 0.56-0.96; P=0.02), the middle quintile (OR 0.77; 95% CI 0.60-0.99; P=0.04), and the second least deprived quintile (OR 0.75; 95% CI 0.56-0.97; P=0.02). Dual eligibility wasn't significantly associated with receipt of MUA (OR 0.72, 95% CI 0.49-1.07, P=11). Conclusion: There were no significant differences for the person-level indicator of deprivation. The most socially deprived quintile had lower odds of MUA receipt than patients in less socially deprived quintiles. While this could be viewed as a positive, alternatively, it may reflect a challenge with postoperative care access and should be further examined.